Strategic Diversification and Core Competence in a Mid-Sized Construction Firm - Wahyu Surya Agung; Harimukti Wandebori; Socrates Rudy Sirait (LPPM STIE KRAKATAU, 2026)
This study examines how a mid-sized Indonesian construction firm can strategically diversify while protecting its core competencies. It uses a sequential explanatory mixed-methods single-case design of WSA Construction + Planning, combining semi-structured interviews and document analysis, triangulated with sector reports and internal performance indicators. Related diversification options that align with market attractiveness and strategic fit, particularly institutional healthcare projects and sustainability consulting, emerge as the most promising paths, whereas unrelated real estate ventures increase strategic and execution risk. The evidence highlights the role of dynamic capabilities in sequencing and integrating diversification moves without diluting the core business. The most defensible approach is phased, competence-adjacent diversification supported by disciplined execution and performance monitoring to safeguard the firm’s distinctive capabilities. As a single-case study, the findings support analytical rather than statistical generalization, and scenario-based projections remain sensitive to implementation quality and market conditions. This article offers an integrated, practice-oriented framework that links external market analysis, VRIN-based capability assessment, and Balanced Scorecard-informed governance to guide diversification decisions in mid-sized construction firms in emerging markets.